Differences in BMI between Mexican and Colombian patients receiving antipsychotics: results from the International Study of Latinos on Antipsychotics (ISLA). Issue 4 (18th May 2020) - Ng, Bernardo; Camacho, Alvaro; Parra, Katherine; de la Espriella, Ricardo; Rico, Victor; Lozano, Severiano; Troncoso, Mirna; Castilla-Puentes, Ruby C.; Cook, Benjamin L.; Jimenez, Daniel E.
ABSTRACT: Objective: The objective of this study is to examine the association of country of residence with body mass index (BMI) between Mexican and Colombian patients exposed to antipsychotics. We hypothesize that there will be a significant association between country of residence and BMI and that Mexican patients will have higher BMI than their Colombian counterparts. Design: The International Study of Latinos on Antipsychotics (ISLA) is a multisite, international, cross sectional study of adult Latino patients exposed to antipsychotics in two Latin American Countries (i.e. Mexico and Colombia). Data were collected from a total of 205 patients (149 from Mexico and 56 from Colombia). The sites in Mexico included outpatient clinics in Mexicali, Monterrey and Tijuana. In Colombia, data were collected from outpatient clinics in Bogotá. For this study we included patients attending outpatient psychiatric community clinics that received at least one antipsychotic (new and old generation) for the last 3 months. A linear regression model was used to determine the association of country of residence with BMI for participants exposed to an antipsychotic. Results: After controlling for demographics, behaviors, biological and comorbid psychiatric variables, there was a significant difference between Colombia vs. Mexico in the BMI of patients exposed to antipsychotics ( β = 4.9; p < 0.05). Conclusion: Our hypotheses were supported. These results suggest that differences in BMI in patients exposed to antipsychotics in Mexico and Colombia may reflect differences in prevalence of overweight/obesity at the population level in the respective countries, and highlights the involvement of other risk factors, which may include genetics.